CORPORATE MANAGEMENT MODELS - Alimjanova Dilrabo (Scholars Digest Publishing, 2023)
In this text, we explored three popular management models: the Matrix Model, Holacracy, and Agile Model. Each of these models has its unique approach to management, aiming to create more effective, efficient, and collaborative workplaces. The Matrix Model combines hierarchical and team-based structures, fostering communication, collaboration, and cross-functional knowledge-sharing across departments. Holacracy, on the other hand, relies on a flat, democratic structure that empowers employees to manage their own work and participate in decision-making collaboratively. Finally, the Agile Model emphasizes flexibility, adaptability, and collaboration, enabling teams to work together in sprints to deliver incremental pieces of large, complex projects. Each model has its strengths and weaknesses, with unique advantages and challenges. Ultimately, choosing the right model depends on the organization's unique goals and needs, as well as its internal culture, structure, and capacity to adapt to change.
Keywords: Matrix Model.Holacracy. Agile Model. Team-based structure. Hierarchical structure. Cross-functional communication. Flat organization. Self-management. Decision-making. Flexibility. Adaptability. Incremental project delivery. Collaborative work. Organizational culture. Change management. Project management. Business value.